HUBUNGAN KUALITAS UDARA RUANG PERAWATAN DENGAN GANGGUAN FUNGSI PARU PERAWAT DI RSUD UNDATA PALU - SULTENG - , Herlina Susanto Sunuh, SKM; , Prof. Dr. dr. Soebijanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Indoor air quality greatly affect to human health, because of nearly 90% of human life are in the room (Susanna, 1998). A total of 400 to 500 million people especially in developing countries dealing with the problem of indoor air pollution (Aditama, 1992). In US, the issue of indoor air pollution was raised when the Environmental Protection Agency (EPA) in 1989 announced a study of indoor air pollution is more severe than in the outdoors. Pollution of this type can even reduce the productivity of labor to the U.S. $ 10 billion (EPA, 2007). Research conducted by Ratiah (2008) found the number of germs that air treatment room - AC shows the number of over 8000 koloni/m3. The aim is to analyze the relationship of air quality room of treatment with the occurrence of lung obstruction nurses in RSUD Undata Palu. This research was carried out with the analytic survey with cross sectional approach. The research samples were nurses on the ward Catelia, Seroja and Bougenville in Palu Undata Hospital totaling 35 people. Data obtained through interviews, observations and measurements were subsequently analyzed by univariate, bivariate and multivariate. The results showed the relationship between air quality against decline in value of %FEV1 very weak. Apparently there were other variables that affect to the impairment value of lung obstruction, such as age, nutritional status and working period amounted to 38.1%. The most influential of the three control variables were years of service, that is equal to 34.2%, meaning the longer the working period a person the greater the decline in its value of %FEV1. Conclusion : The relationship between dust level, temperature, humidity and number of germ against of lung obstruction of nurses in RSUD Undata Palu are not significant.